Crafting an occupational identity : Learning the precepts of craftsmanship through apprenticeship - Chan, Selena [Verfasser] (My University, 2014)
"The term craftsmanship is associated with pre-industrial craft work with inferences to skilled artisanal manufacture of bespoke products. Apprenticeship learning is often perceived to be synonymous with learning craftsmanship. How then is the trait of craftsmanship through attainment of specific artisanal approaches conveyed and learnt through apprenticeship? This article presents and discusses processes imposed on and utilised by apprentices to attain precepts of artisanal approaches. The dispositional and skill elements of craftsmanship are proposed to be adopted through engagement with and development of craft and workplace specific approaches to contend with aspects of Pye's (1968) conceptualisation of 'workmanship of risk' or the article's proposed term of 'artisanal approach of risk'." (Authors' abstract, BIBB-Doku)
Keywords: L 3 Lehr-Lern-Forschung; Lehr-Lern-Forschung; Handwerksberuf; Berufsausbildung; Berufliche Identität